PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS DIGITAL TERHADAP HASIL BELAJAR SISWA DI KELAS V SD NEGERI 060938 MEDAN - Resta Marbun; Anton Sitepu; Frikson Jony Purba; Eka Kartika Silalahi; Irmina Pinem; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using interactive digital-based learning media on the learning outcomes of fifth-grade students at SDN 060938 Medan in the 2024/2025 academic year. This research employed a quantitative method, with the study population consisting of all fourth-grade students at SDN 060938. The research sample comprised 28 students selected through purposive sampling techniques. Data on the use of interactive digital-based learning media were obtained through questionnaires distributed to students, while learning outcomes were measured using students' pretest and posttest scores during the 2024/2025 academic year. The results of this study indicate that student learning outcomes using the The use of interactive digital based learning model fall into the "very good" category, with an average posttest score of 82.73 and an average questionnaire score of 86.29. Furthermore, hypothesis testing showed that the calculated t-value (6.282) was greater than the t-table value (2.060), indicating that Ho was rejected and Ha was accepted. Based on the t-test results, it can be concluded that interactive digital-based learning media have a significant effect on the learning outcomes of fifth-grade students at SD Negeri 060938 Medan in the 2024/2025 academic year.